From Private to Religious Patriarchy: Gendered Consequences of Faith-Based Welfare Provision in Germany - Josef Hien (Religion and Politics, 2017)
Over one million people work for a faith-based welfare provider in Germany. Caritas and Diakonie, the largest faith-based providers in Germany enjoy prerogatives that do not exist in other countries. This particular group of faith-based organizations is exempt from federal labor law and discrimination clauses, which results in arbitrary, and in other cases, institutional, forms of discrimination against particular social groups in society. Research has focused on the institutional regulation of faith-based practice in Germany. Much less attention has been devoted to the faith component within faith-based welfare provision. This study traces the evolution of church doctrine and its impact on the care and employment practices of faith-based welfare providers in Germany from the 1950s to the present. It argues that the conservative ideology of these welfare providers amplifies the negative effects of gendered occupational regimes.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; patriarchy; religion; gender-specific factors; welfare state; Federal Republic of Germany; social policy; religious factors; welfare organization